THE COMPARATIVE ANALYSIS OF THE LEXICAL AND STRUCTURAL FEATURES OF BULGHATIL MUSHTAQ AND TARJUMAN TURKI - Ganiyeva Barchinoy (American Journals, 2025)
This study presents a comparative analysis of two 14th-century Mamluk-era Turkic–Arabic bilingual dictionaries, Bulghatil Mushtaq by Jamal al-Din al-Turki and Tarjuman Turki. Both manuscripts, composed in scholarly style, reflect the linguistic, cultural, and social dynamics of their time. The analysis demonstrates that while the lexical composition of the two works is largely similar, they differ significantly in the methods of translation, degree of explanation, thematic organization, and intended audience. Bulghatil Mushtaq provides concise single-word translations of complex terms, particularly in scientific and military domains, indicating its orientation toward the educated elite. In contrast, Tarjuman Turki offers extensive explanatory glosses, cultural notes, and etymological references, suggesting that it functioned as a more accessible guide for multilingual communities. Comparative examination of thematic sections further reveals differences in structural arrangement, with Tarjuman Turki covering a broader range of categories.
Keywords: Bulghatil Mushtaq, Tarjuman Turki, Mamluk period, comparative linguistics, lexical structure, etymology, scientific terminology.